The effect of different feedback frequency on throwing performance among children / Muhammad Anwar Ahmad - Ahmad, Muhammad Anwar (2017)
Feedback has been one of the most important factors that affect motor performance. The implementation of feedback frequency has been proven to enhance the acquisition and retention phase of motor performance in individuals. A lot of studies that had been performed showed significant different with the application of this medium. However, there is still lack of studies that conducted in children to prove the effectiveness and efficiency of this medium among children. Thus, the purpose of this study was to determine the effects of different feedback frequency on throwing performance among children. Forty-five children were recruited in this study. Participants were divided into three different frequency of feedback group (0%, 50% and 100%). Each participant was given task to throw beanbags to a target placed on the floor by using their non-dominant arm while the eye sight was limit by wearing an opaque goggle and feedback frequency was given to the participants according to the specific feedback group and then the tasks performance was measured through throwing test. Significant different were found on acquisition phase (p < 0.05) in which the results showed the performance in 100% of feedback frequency group were better than the other groups. Thus, this finding revealed that 100% of feedback frequency can significant enhance the throwing performance among children on acquisition phase. Continuous feedback led to a better performance · within the acquisition phase compared to the non-continuous form because extra frequently feedback allows individuals to exploit the acquired information to well learn the task's key strategies and to mend their performance.